Acute postoperative pain management in the older patient. (December 2011) - Hallingbye, Thor; Martin, Jacob; Viscomi, Christopher
Acute pain management in the older adult is both challenging and rewarding. This review addresses the difficulty with assessment of pain in the older adult, variations in the pain experience of older adults, physiological differences between the young and old, changes in pharmacokinetics and pharmacodynamics with age, and useful pharmacological treatments for acute pain in older adults. It then presents a few representative cases of pain management in older adults. The goal of this review is to provide relevant information that can be used to manage acute postoperative pain in the older adult.